2018
DOI: 10.1002/asmb.2342
|View full text |Cite
|
Sign up to set email alerts
|

Integrative interaction analysis using threshold gradient directed regularization

Abstract: For many complex business and industry problems, high‐dimensional data collection and modeling have been conducted. It has been shown that interactions may have important implications beyond the main effects. The number of unknown parameters in an interaction analysis can be larger or much larger than the sample size. As such, results generated from analyzing a single data set are often unsatisfactory. Integrative analysis, which jointly analyzes the raw data from multiple independent studies, has been conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…First developed for linear regression [ 3 ] and later extended to many other regression models [ 30 , 31 , 35 ], TGDR is a generically applicable regularized optimization technique. The key strategy is that, in gradient-based optimization, in each iteration, gradients are compared and important parameters with large gradients identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First developed for linear regression [ 3 ] and later extended to many other regression models [ 30 , 31 , 35 ], TGDR is a generically applicable regularized optimization technique. The key strategy is that, in gradient-based optimization, in each iteration, gradients are compared and important parameters with large gradients identified.…”
Section: Methodsmentioning
confidence: 99%
“…In regression analysis of multiple types of responses under various models, it has been shown that TGDR has an intuitive formulation, simpler computation, and satisfactory estimation and selection performance. Beyond “standard” settings, it has also been extended to complex data/model settings, for example, longitudinal data [ 29 ], interaction analysis [ 30 ], multidataset analysis [ 31 ], and others [ 32 ]. It has been shown that, for many data settings, TGDR outperforms penalization, Bayesian, boosting, and other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…15 Li et al. 19 proposed TGDR for integrative interaction analysis. The model they considered, however, is a parametric one.…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of methodology, we developed a novel TGDR for semiparametric integrative interaction analysis, as an extension to the work by Li et al. 19 Moreover, data on other cancers in TCGA have characteristics similar to those of NSCLC: multiple datasets, high dimensionality, a small sample size, gene–gene interactions, and environmental factors. Consequently, the proposed approach can be seen as a general method of analysing cancer data.…”
Section: Introductionmentioning
confidence: 99%
“…To further examine the stability of the performance in screening and feature selection of these methods, we calculate the observed occurrence index (OOI). 42 A resampling of 100-times generates 100 new samples. Each sample includes the new design matrix X and the corresponding responses Y .…”
Section: Skcm Data Analysismentioning
confidence: 99%